CLASSIFICATION AND ANALYSIS OF MEDICAL WASTE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
For medical waste, depending on the class, different requirements for collection, temporary storage and transportation apply. It is not allowed to mix medical waste of different classes at any stage of collection and storage.Disposal of medical waste is also determined on the basis of their class, even just transportation, removal of medical waste must be carried out in accordance with the rules for waste management in accordance with.